Expression of MRP8/MRP14 mRNA in Monocytes of Periodontitis: Comparison between Diabetic and Non Diabetic Patients - Ahmad Syaify; Sri Budi Barunawati; Suryono Suryono; Marsetyawan HNES (The Indonesian Journal of Dental Research, 2010)
The severity of periodontitis on patients with type 2 Diabetes Mellitus patients was strongly thought caused by decreasing of leukocytes function such as monoctyes and neutrophils. In our previous research it was found that calprotectin (MRP8/MRP14) level in leukocytes of periodontitis patients with type 2 DM was higher than periodontitis in non DM. The aim of this study was to determine calprotectin (MRP8/MRP14)mRNA expression in human monocytes of periodontitis patients with type 2 DM and without DM. Monocytes were isolated from the peripheral blood of periodontitis patients with uncontrolled type 2 DM, controlled type 2 DM, and non DM. The expression of total RNA calprotectin (MRP8 and MRP14) were detected by RTPCR using GAPDH as the innate control. It was observed that the value of MRP8/MRP14 mRNA expression DM patients were higher than non DM, and the highly significant increase expression (p<0.05) was on the uncontrolled type 2 DM. The basal level of MRP8/MRP14 expression increased in monocyte of periodontitis and type 2 DM patients compared with non diabetes subjects. It was suggested that high basal level MRP8/MRP14 has role in the regulation of severity periodontitis with diabetes mellitus.